Wealth Study of Types Of Rats On Natural And Made In Ecosystems In Bengkulu Province - Rizwar S (Talenta Publisher, 2019)
Rats are cosmopolitan animals because they are able to adapt to environmental changes. These small mammals can be found from primary and secondary forests, plantation areas, rice fields to human settlements. The species richness, distribution, size and dynamics of rats in an ecosystem are determined by external factors such as climate, season, availability of food, habitat / ecosystem type, barrier, type of vegetation cover, soil type, competition, predation and internal factors such as age structure and fertility. This study aims to analyze the richness of rats in natural ecosystems such as secondary forests, swamp forests, grasslands and artificial ecosystems such as palm plantation ecosystems, rubber plantations and rice field ecosystems in Bengkulu Province. The study is located around Bengkulu University, Rojolelo Park, palm plantation of PT. Bio Nusantara, North Bengkulu regency and Mekar Jaya village in Muko-Muko Regency. The study was conducted for four (4) months from April to August 2016. Rats were collected using clamps traps and all traps placed in the study areas used purposive sampling method. The results of the study found five (5) species of rats occupying different ecosystems, namely Rattus tiomanicus, R. exulans, R. argentiventer, R. novergicus and Mus musculus castaneus. Species of R. tiomanicus and R. exulans are cosmopolitan species that occupy all types of ecosystems. R. argentiventer are characteristic in rice field ecosystem, R. novergicus occupies only palm and rubber plant ecosystems while Mus musculus castaneus is found only in palm and paddy field ecosystem.